Pengaruh Faktor Safety Culture, Safety Management System dan Pemandu Lalu Lintas Penerbangan Terhadap Keselamatan Penerbangan di Perum LPPNPI Cabang Matsc - Ananda Zahra Salsabil; Arif Fakhrudin (IAI Nasional Laa Roiba Bogor, 2024)
Aviation incidents can be in the form of Break of Separation (BOS) or Break of Coordination (BOC). At the LPPNPI MATSC Branch, there are deficiencies or obstacles in fulfilling flight safety levels. It can be seen from the number of BOS and BOC. It is known that the number of BOS and BOC occurring at Perum LPPNPI MATSC Branch has increased. The incident that occurred was one of the lack of implementation of Safety Culture towards the optimal implementation of Air Traffic Services, identifying symptoms of accidents that could occur due to human error. This research is included in quantitative research, with a sample size of 40 respondents using probability sampling techniques. Then the data was analyzed using validity tests, reliability tests, t tests, F tests and coefficient of determination tests. The results of this research include: 1) H1 is accepted, meaning there is an influence of safety culture factors on aviation safety at PerumLPPNPI Matsc Branch, 2) H2 is declared accepted, which means there is an influence of the Safety Management System on aviation safety at PerumLPPNPI Mats Branch, 3) H3 is declared rejected, which means There is no influence of aviation traffic guides on aviation safety at PerumLPPNPI Matsc Branch, 4) there is an influence of safety culture factors, safety management systems and aviation traffic guides on aviation safety at PerumLPPNPI Matsc branch 5) The R square value is 0.572 which can be interpreted as meaning that The influence of safety culture factors, safety management systems and aviation traffic guidance is very strong on aviation safety.